Details of a non-fatal human-crocodile interaction in the Laguna del Carpintero, Tampico, Mexico - César N. Cedillo-Leal; Gabriel Barrios-Quiroz; Sergio E. Padilla-Paz (Neotropical Biology and Conservation)
Human-crocodile interaction in the Laguna del Carpintero, Tampico, Tamaulipas, Mexico has been a growing concern for the last several years, with homeless people being the most affected, although individuals of fixed address have also been involved. The objective of this document is to describe in detail a case of non-fatal human-crocodile interaction in this lagoon and the response of the SOS Crocodile Tampico working group. To document the case, we collected information on the interaction, the causative crocodile and the affected person. On June 8, 2024 a male person was involved in a non-fatal interaction with a 278 cm long crocodile, which caused a fracture in his left leg, requiring him to be transported to the nearest hospital. This event activated the first response team who provided pre-hospital and hospital care; search and capture of the crocodile involved, as well as the custody, handling and final disposal of the crocodile into captivity. Therefore, we consider that inter-institutional coordination between federal, state, municipal, health and crocodile specialists, integrated as the SOS Crocodile working group, is fundamental to rapidly and efficiently attend the interactions with crocodiles in urban areas.